COMMUNICATION STRATEGIES OF WOMEN LEADERS IN AI-BASED DIGITAL TRANSFORMATION IN TRANSFORMATIONAL LEADERSHIP PERSPECTIVES AND SENSEMAKING - Ni Putu Limarandani; Ira Tundjungsari; A.A Ketut Patera (Lektur: Jurnal Ilmu Komunikasi, 2026)
The development of Artificial Intelligence (AI) has driven digital transformation that is not only technological in nature but also communicative and symbolic within organizations. This transformation requires leadership capable of managing meaning, building collective understanding, and directing change through communication processes. This study aims to examine the communication strategies of women leaders in AI-based digital transformation using the perspectives of transformational leadership and sensemaking theory. This study employs a qualitative approach, with the primary informant being Dr. Ir. Giwo Rubianto Wiyogo, M.Pd., President of BPW Indonesia, supported by two additional informants Fiyatri Widuri, S.T., Vice President of Business Professional Women (BPW) Indonesia, and I Dewa Ayu Dania Adnyani, an organizational partner of BPW Indonesia as a form of source triangulation. Data were collected through in-depth interviews, observation, and document analysis, and subsequently analyzed using thematic and interpretative techniques. The findings indicate that women’s leadership communication strategies are articulated through the formulation of a transformational vision, the use of inclusive narratives and communicative symbols, and dialogical communication practices that encourage participation and collective learning. Leadership communication functions as a mechanism for constructing shared meaning about AI, reconstructing organizational members’ perceptions from uncertainty toward understanding and readiness for transformation. Conceptually, this study extends leadership communication scholarship by positioning AI-based digital transformation as a communicative process mediated by women’s leadership